A mathematical model of the apparent mass of the human body under fore-and-aft whole-body vibration - Nawayseh, N. (International Journal of Automotive and Mechanical Engineering, 2022)
Studies of biodynamic responses to vibration have mainly focused on vertical vibration, despite the presence of high fore-and-aft and lateral vibration in some vibration environments. Consequently, models of the biodynamic responses to vibration in directions other than vertical are rare. This paper presents a model of the apparent mass of the human body during fore-and-aft vibration. The model is a two-degrees-of-freedom lumped parameter linear model with translational and rotational capabilities. The parameters of the model were optimised using experimentally measured apparent mass. The model gave a close fit to the measured apparent masses of 12 subjects. The parameters of the rotational degrees-of-freedom showed high variability, reflecting the high variability found in the measured data for the 12 subjects. Sensitivity analysis showed that the first peak of the apparent mass is produced by rotational motion while the second peak is caused by translational motion. This study showed that the fore-andaft apparent mass of the human body can be represented by a two-degrees-of-freedom system with rotational and translational capabilities. The proposed model can be integrated with a mathematical model of a seat to predict the transmissibility of the seat. Alternatively, the model parameters can be used to build a mechanical dummy that can be used experimentally for seat testing applications instead of using a human subject.